PENGARUH KOMUNIKASI POLITIK APARATUR PEMERINTAH TERHADAP PELAYANAN PUBLIK - Akhirul Aminulloh; Dody Setyawan (REFORMASI, 2013)
Political communication aspirational government officials will bring a harmonious relationship between government officials and the public, so as to improve public services better. Communication also makes good political government policy based on the aspirations of the community, and the community will participate in any policy made by the local government because they feel involved. This research was conducted in Malang by using quantitative methods with simple linear regression analysis. Determination of sampling using purposive sampling technique. The data analysis with SPSS to test the research hypothesis. The results of this study stated that the Political Communication and a significant positive effect on the Public Service.